IMPROVING SCHOOL PRINCIPAL COMPETENCE IN IMPLEMENTING ACADEMIC SUPERVISION THROUGH MONITORING AND EVALUATION METHODS IN INDRAGIRI HULU REGENCY - Sartana Sartana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the large number of principals who do not conduct supervision and evaluation on academic supervision in schools because they just served as principal so that the quality of learning becomes low. For this reason, this study aims to improve the competency of principals in carrying out academic supervision through monitoring and evaluation. This research was an action research conducted at 10 primary school principals in Indragiri Giri Hulu. The instrument used was in the form of observation sheet to observe the implementation of supervision which was used as material for analysis and follow-up improvement in the competency of the principal. The results of the study found that the implementation of academic suprervision in the first cycle was 77% which meant the competence of principals included in the enough category while the second cycle increased to 88% which included in good category. Based on the results of the study, it can be concluded that the competency of principals in Indragiri Hulu in implementing academic supervision has increased through monitoring and evaluation.